Mycotoxigenic potential of fungi isolated from freshly harvested Argentinean blueberries - Munitz, Martín Sebastián (2014)
Alternaria alternata, A. tenuissima, Fusarium graminearum, F. semitectum, F. verticillioides, Aspergillus flavus, and Aspergillus section Nigri strains obtained from blueberries during the 2009 and 2010 harvest season from Entre Ríos, Argentina were analyzed to determine their mycotoxigenic potential. Taxonomy status at the specific level was determined both on morphological and molecular grounds. Alternariol (AOH), alternariol monomethyl ether (AME), aflatoxins (AFs), zearalenone (ZEA), fumonisins (FBs), and ochratoxin A (OTA) were analyzed by HPLC and the trichotecenes deoxynivalenol (DON), nivalenol (NIV), HT-2 toxin (HT-2), T-2 toxin (T-2), fusarenone X (FUS-X), 3-acetyl-deoxynivalenol (3-AcDON), and 15-acetyl-deoxynivalenol (15-AcDON) by GC. Twenty-five out of forty two strains were able to produce some of the mycotoxins analyzed. Fifteen strains of Aspergillus section Nigri were capable of producing Fumonisin B1 (FB1); two of them also produced Fumonisin B2 (FB2) and one Fumonisin B3 (FB3). One of the F. graminearum isolated produced ZEA, HT-2, and T-2 and the other one was capable of producing ZEA and DON. Two A. alternata isolates produced AOH and AME. Four A. tenuissima were capable of producing AOH and three of them produced AME as well. One Aspergillu flavus strain produced aflatoxin B1 (AFB1), aflatoxin B2 (AFB2), and aflatoxin G1 (AFG1). To our knowledge, this is the first report showing mycotoxigenic capacity of fungal species isolated from blueberries that include other fungi than Alternaria spp.